The Urban-rural Continuum: A New Approach to the Future Planning for Rural China - Lin, Mao (European Journal of Sustainable Development, 2020)
China’s urbanization has brought benefits to cities, but the price is the deterioration of the urban ecological environment. As a result of long-term urban-rural dualism, China has actively supported cities, and then cities have occupied nature-based rural areas. Even though China has been aware of the ecological deterioration and has issued rural ecological policies, there is still the existing contradiction between urban expansion and rural protection development. China’s future planning will place greater emphasis on rural areas, and people have just entered the exploration phase. In this regard, the theory of “the urban-rural continuum” proposed by an American anthropologist William Skinner is extended to the field of architecture and planning to explore a sustainable method of urban-rural development. It offers a spatial model to describe China’s traditional social structure, from villages to cities, combined by the community of a standard market town. It underlies a polycentric model with a communal structure that can further balance the urban-rural relationships and realize the sustainable development in the countryside. Keywords: the urban-rural continuum, green city, community, sustainable planning, rural heritage